Ethnic tourism potential of Bukovyna for the purposes of cross-border tourism - Buchko, Zhanna; Rudenko, Stepan; Rudenko, Valeriy; Yeremiia, Hanna (Human Geography Journal, 2016)
The goal of this paper is to study the prospects of use of ethnic and cultural potential at the trans-boundaryterritoryofChernivtsiregion inUkraineand Suceava region inRomania. (Ethnical and cultural region known asBukovina). Our work relies on systematization and synthesis of the empirical data about practical transboundary tourism projects inBukovina. The author was discovered general trends formation of conditions for improvement in the region ethnotourist routes broadest possible use of the existing network of museums, centers and folk venues ethnic holidays and festivals. Ethnic resources ofBukovinaas constituent of ethnographic tourism are observed. Material and spiritual culture of Bukovinians in the context of Ethnic tourism are analyzed. The scientific novelty of our work is evaluation of the use of museums and centers of handicrafts in tourism, retrospective analysis of folk-ethnographic holidaysBukovinaand evaluation for the purposes Ethnic tourism. The practical significance of this research is the possibility of implementation of the proposed concepts into the planned tourism activity in accordance with the formal development programs and strategies accepted in Chernivtsi region. Further implementation of our work will be development of transboundary routes in Chernivtsi and Suceava region based on the means of underlying theme.